High‐Performance W‐Band Mhemt Low Noise Amplifier using Millimeter‐Wave Tuner System. Issue 9 (27th June 2013) - An, Dan; Rhee, Jin‐Koo
ABSTRACT In this article, we report a high‐performance W‐band metamorphic high electron‐mobility transistor (MHEMT) low noise amplifier (LNA) using millimeter‐wave tuner system. The MHEMT devices for millimeter‐wave monolithic integrated circuit LNA exhibited the current gain cutoff frequency (fT) and maximum oscillation frequency (fmax) were 195 and 305 GHz, respectively. The accurate noise parameter was extracted using millimeter‐wave tuner system to design the W‐band LNA. The fabricated W‐band LNA represented S21 gain of 7.42 dB at 94 GHz and noise figure of 2.8 dB at 94.2 GHz. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2157–2160, 2013